Pemanfaatan Pemberian Permen Jahe Terhadap Mual Muntah Pada Ibu Hamil di Puskesmas Sidodadi Tahun 2022 - Maidina Putri; Siti Maimunah; Eka Vicky Yulivantina (Cv. Utility Project Solution, 2022)
Nausea and vomiting (Emesis Gravidarum) are symptoms that often appear in every pregnancy. Nausea usually occurs in the morning, but can also occur every day and night, this occurs due to relaxation of the digestive muscles, including peristalsis in the stomach so that digestion of food by the stomach takes longer and peristalsis easily occurs back into the esophagus, besides that the influence of the HCG hormone. In the working area of the Sidodadi Health Center there are 48 pregnant women and on average they experience nausea and vomiting during their pregnancy. Providing counseling about the use of giving ginger candy to pregnant women is very appropriate to do in the Sidodadi Health Center area, this is also supported by the area where the average is a farmer and every household uses their land to grow spice plants such as ginger, turmeric, serer trees, galangal and others. The method that will be used in achieving this goal is to approach the community, outreach, and direct application with the community about the benefits of ginger candy during pregnancy.